Artificial Photosynthesis over Tubular In2O3/ZnO Heterojunctions Assisted by Efficient CO2 Activation and S‐Scheme Charge Separation. (11th November 2022) - Han, Gaowei; Liu, Chengyuan; Pan, Yang; Macyk, Wojciech; Wageh, Swelm; Al‐Ghamdi, Ahmed A.; Xu, Feiyan
Abstract: Solar‐driven CO2 reduction shows promise in alleviating climate change and energy crises, but it suffers from difficult CO2 activation and rapid electron/hole recombination in current photocatalysts. Here we develop novel metal‐organic frameworks (MOFs)‐derived In2 O3 /ZnO tubular S‐scheme heterojunction photocatalyst for CO2 photoreduction. Resulting from Fermi level difference and electron transfer, an internal electric field is built at heterojunction interfaces and contributes to the formation of S‐scheme heterojunctions, as unveiled by in situ irradiation X‐ray photoelectron spectroscopy and time‐resolved photoluminescence spectroscopy. CO2 molecules are chemisorbed and activated over the photocatalyst in views of DFT simulations. The CO2 photoreduction follows a *COOH‐intermediate pathway and affords an enhanced CO production rate (12.6 µmol g −1 ) with nearly 100% selectivity in the absence of any molecular cocatalyst or scavenger. The enhanced performance is ascribed to the efficient charge separation, stronger redox ability, and powerful CO2 activation of In2 O3 /ZnO S‐scheme heterojunctions. Abstract : Unique MOF‐derived In2 O3 /ZnO tubular S‐scheme heterojunctions afford improved CO2 photoreduction performance in the absence of any molecular cocatalyst or scavenger, ascribed to the efficient charge separation, strong redox ability of survived charge carriers, and excellent CO2 activation capability.